Analyzing the influence factors of the carbon emissions from China's building and construction industry from 2000 to 2015 - Wu, Peng; Song, Yongze; Zhu, J.; Chang, R. (2019)
China has been the largest contributor to global carbon emissions since 2008, with its building and construction industry considered as one of the most significant sources. However, few studies have been conducted on analyzing the influencing factors of the carbon emissions following a life cycle perspective. This study aims to evaluate the carbon emissions of this industry from a life cycle perspective, including the extraction, manufacturing, construction and construction-related transportation, and building operation, using Logarithmic Mean Divisia Index. The key findings are: 1) the extraction and manufacturing of raw materials, and building operation are the two biggest contributors to the life cycle carbon emissions of the building and construction industry, accounting for 58% and 40% respectively; 2) the most effective strategies to reduce carbon emissions in the construction stage from 2000 to 2015 are to improve energy efficiency and lower emission factor; and 3) the most effective strategies to reduce carbon emissions in the building operation stage from 2000 to 2015 are to increase development density, improve emission factor, energy structure and industry structure. This study provides useful scientific evidence for policy makers to establish appropriate emission targets and relevant reduction strategies that are relevant to China's building and construction industry.